Three learning environments to stimulate creativity: Case School of Design at North Carolina State University - Angulo, Camilo A.; Universidad Jorge Tadeo Lozano (Universidad Católica de Pereira, 2016)
This document presents three main reflections on learning. They were the result of an educational observation at the School of Design at North Carolina State University in the United States, during the fall semester of 2013. These environments promote multicultural academic teaching and design learning by stimulating the development of creative minds inside and outside the classroom.